المسؤولية القانونية عن سوء ممارسة الطب التقليدي (الشعبي) دراسة مقارنة بين ماليزيا والعراق - عطية، أسماء إبراهيم (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
This study examines and compares the liability for malpractice in using traditional medicine in Malaysia and Iraq, academically, legally and judicially. It states the structure and rules for legal liability in the malpractice of using traditional medicine in order to draw the general framework of this liability in Malaysia and Iraq. The study is based on a number of research methods: inductive and analytical method was used to present and analyzes the professional, legal and judicial rules related to legal liability for malpractice of traditional medicine in the legislation of some countries in general, and Malaysian and Iraqi legislation in particular in order to draw the basic features of this liability. Another method applied was comparative approach was also used to identify similarities and differences in this liability between Malaysia and Iraq. Besides the critical method in observing the glitches and weaknesses of these rules and in showing their advantages and disadvantages in order to enrich Malaysia and Iraq in establishing the principles and provisions of this liability. Finally, the applied method was used through examining several models of professional and judicial applications in malpractice of this medicine in legislation, highlighting such liability, including in the United States, Britain, Australia, China and Singapore in order to take advantage of these legislation in structuring the rules of this liability in both Malaysia and Iraq. The most important finding of this research is the lack of professional and legal regulation and the lack of judicial principles facing malpractice cases in using traditional medicine, whether in Malaysia or Iraq. Based on the research results, the researcher recommends establishing an independent professional, legal and judicial system to draw the legal liability framework for malpractice of traditional medicine in international legislation generally and Malaysian and Iraqi legislation especially.